Minimally invasive treatment of transorbital penetrating injury of skull base and cavernous sinus – A case report - Jelača, Bojan; Djilvesi, Djula; Papić, Vladimir; Pajičić, Filip; Lepić, Milan; Vuleković, Petar (Vojnosanitetski pregled, 2022)
Introduction. A transorbital intracranial injury with a foreign body can be a very complex and controversial therapeutic problem. The orbit's content is susceptible to penetrating trauma, and neurovascular skull base structures are at high risk from injury. There are some traditional cranial surgical approaches and more recently reported different endoscopic approaches for treating this kind of injury. Case report. We presented a case of a 30-year-old male who had an accident at work when a piece of wood hit him in his head and entered through the medial aspect of his left orbit with skull base and cavernous sinus injury. Rapid and complete radiological and clinical assessments were performed, and the patient was treated in a minimally invasive manner. The foreign body was manually extracted with an endoscopic and endovascular team ready to treat adverse events. No postoperative complications were reported, and visual acuity increased at the one-month follow-up. Conclusion. Penetrating wounds of the orbit represent a challenge that requires a multidisciplinary assessment and well-organized management. Combined endoscopic minimally invasive approaches should be considered during the treatment of this kind of injury.
Keywords: decompression, surgical; head injuries, penetrating; minimally invasive surgical procedures; neurosurgical procedures.